Guatemala : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Guatemala. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper focuses on Guatemala's Request for Purchase Under the Rapid Financing Instrument. The coronavirus disease 2019 pandemic is severely impacting Guatemala. Faltering external demand, declining remittances, and the necessary lockdown and social distancing to contain the virus, have disrupted economic activity and severely worsened external and fiscal positions. IMF support under the Rapid Financing Instrument will help address the urgent balance of payments and fiscal needs, improve confidence, and catalyze support from other external partners. In order to support the recovery and counter future shocks, the authorities intend to maintain an accommodative monetary policy stance and exchange rate flexibility. While credit risk regulations have temporarily been eased to facilitate loan restructuring, the authorities are closely monitoring banks' exposures and the levels of provisioning to ensure the stability of the financial system. The Guatemalan authorities have reaffirmed their commitment to ensure that emergency financing is used effectively, transparently, and through reinforced governance mechanisms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet